2010
DOI: 10.1186/1471-2164-11-624
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the temporal host response to skin infestation with the ectoparasitic mite Psoroptes ovis

Abstract: BackgroundInfestation of ovine skin with the ectoparasitic mite Psoroptes ovis results in a rapid cutaneous immune response, leading to the crusted skin lesions characteristic of sheep scab. Little is known regarding the mechanisms by which such a profound inflammatory response is instigated and to identify novel vaccine and drug targets a better understanding of the host-parasite relationship is essential. The main objective of this study was to perform a combined network and pathway analysis of the in vivo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 156 publications
(191 reference statements)
4
69
0
Order By: Relevance
“…A similar result was also described by Hammad et al, [63]. We recently confirmed the findings of previous studies which identified the presence of a P. ovis homologue of Der p 2 (termed Pso o 2) which, like Der p 2, contains a conserved MD-2-related lipid-recognition (ML) domain and has 41% amino acid identity with Der p 2 [11], [64], [65]. Pso o 2 also maintains a number of important features deemed to be necessary for MD-2 like activity, including six conserved cysteine residues, N-glycosylation sites and conserved lysine residues involved in binding LPS [60], [61], [66].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A similar result was also described by Hammad et al, [63]. We recently confirmed the findings of previous studies which identified the presence of a P. ovis homologue of Der p 2 (termed Pso o 2) which, like Der p 2, contains a conserved MD-2-related lipid-recognition (ML) domain and has 41% amino acid identity with Der p 2 [11], [64], [65]. Pso o 2 also maintains a number of important features deemed to be necessary for MD-2 like activity, including six conserved cysteine residues, N-glycosylation sites and conserved lysine residues involved in binding LPS [60], [61], [66].…”
Section: Resultssupporting
confidence: 91%
“…The triggering of this rapid and extensive inflammatory response by mite-derived factors is clearly of central interest in elucidating the initiation of the immunopathology associated with sheep scab. A previous study by our group demonstrated that expression of key members of the TLR4-signalling pathway including TLR4, MYD88 and CD14 where all up-regulated in sheep skin within a few hours of exposure to P. ovis , thus implicating an LPS-type response resulting in the activation of NF-kB and AP-1 [11]. The triggering of innate immune receptors by parasites is not novel, for example the parasitic nematode Acanthocheilonema viteae (via the ES62 molecule) and the parasitic trematode Schistosoma mansoni [via lacto-N-fucopentaose III (LNFPIII)] have been shown to induce NF-kB-mediated immune responses by activating the TLR4-signalling pathway [58], [59].…”
Section: Resultsmentioning
confidence: 86%
“…HDM Der p 3 allergen is a 30 kDa serine protease with trypsin-like activity that is able to enzymatically digest the complement components C3 and C5, generating the anaphylatoxins C3a and C5a, thus contributing to the pathogenesis of allergic disease [41]. We have previously demonstrated the involvement of the complement system in the host response to P. ovis [6] and the identification of a Der p 3 homologue in P. ovis adds further support to this finding. The identification of a Der p 21 homologue is a significant finding and could indicate a novel mechanism by which P. ovis interacts with the host immune response.…”
Section: Resultsmentioning
confidence: 78%
“…Mites abrade the cuticle and deposit allergens when establishing themselves on the host, that results in severe inflammatory responses [13, 14] and the production of an exudate that, in turn, represents a food source for the mites [15]. Features of psoroptic mange include intense pruritus, extensive dermatitis, depilation and hyperkeratosis, which ultimately result in emaciation or death caused by secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%